PLATELET-RICH PLASMA (PRP) TO TREAT CHRONIC UPPER PATELLAR TENDINOPATHIES. Issue 10 (10th June 2013) - Kaux, J F; Croisier, J L; Bruyère, O; Rodriguez, C; Daniel, C; Godon, B; Simoni, P; Alvarez, V; Brabant, G; Lapraille, S; Lonneux, V; Noël, D; et al.
Abstract : Background: Upper patellar tendinopathies remain often chronic and rebel to a thorough conservative treatment. Moreover, the option of a surgical treatment could be disappointing. New treatments are being developed. Injection of PRP is one of these. Platelets contain lot of growth factors which would have the potentiality to enhance the healing process of tendons. Even if in vitro and animal experiments have demonstrated this stimulation of tendon healing process, 1 clinical series are subject to controversy. 2 Methods: Twenty patients with chronic upper patellar tendinopathy were enrolled. Assessments [VAS, clinical examination with an algometer, algofunctional scores (IKDC and VISA-P), functional assessments (isokinetic and Optojump) and imagery (ultrasounds and MRI)] were made before infiltration of PRP, and 6 weeks and 3 months after. The PRP was obtained by an apheresis system (COM.TEC, Fresenius). Six millilitres of PRP were injected without local anaesthetic. One week after infiltration, patients started a 6-week standardised sub-maximal eccentric reeducation. Results: We observed a very significant improvement of the algofunctional status as soon as 6 weeks after the infiltration of PRP, and continued to a lesser extent up to 3 months. During functional evaluation, pain decreased as well, but without significant improvement of performances. No significant improvements in the imagery were observed. Interestingly, patients who had a VAS equal or below 1 after 3 months post-infiltration were younger (24.7 vs 32.2 y.o.). Moreover, these younger patients had a significant increase of the IKDC score (p=0.003), a significant improvement of pain during isokinetic evaluations (p<0.05), and during Optojump assessments (p=0.01). Seventy-five percent of subjects were able to return to sport, even if only half of these patients recovered the same level than before the tendinopathy. Discussion/Conclusions: This study demonstrates that a local infiltration of PRP associated with a submaximal eccentric protocol is efficient to improve symptoms of chronic upper patellar tendinopathies, non-responsive to classical conservative treatments. However, up to now, there is no consensus on the method to prepare the PRP. Indeed, each technique could provide a very different PRP (variations in the platelet concentrations and of the amount of red and white cells).